AB0626 Clinical Predictors for Development of Interstitial Lung Disease in Mctd. (15th July 2016) - Narula, N.; Narula, T.; Wang, B.; Abril, A.
Abstract : Background: Mixed connective tissue disease (MCTD) is an immune-mediated systemic disorder characterized by serum autoantibodies against U1-ribonucleoprotein and diverse multi-systemic clinical manifestations. Approximately 50% of patients with MCTD develop a radiological pattern of interstitial lung disease (ILD). In this study, we explore the phenotypic and clinical features in patients with MCTD that are associated with development of ILD. Objectives: To explore the association of demographics, clinical features and serologic markers with the development of ILD in patients with MCTD. Methods: We performed a retrospective case control study utilizing data from patients evaluated at a single tertiary care center between 2007–2014. Twenty-eight patients who met validated criteria for diagnosis of MCTD were included in the study. Out of these, 14 patients had high-resolution computed tomography or biopsy-proven ILD, and the remaining 14 had MCTD without any evidence of ILD. We performed a multivariate logistic regression with multiple demographic, clinical and serological predictor variables, and ILD as the outcome variable. Results: Two clinical variables were found to have an association with development of ILD in patients with MCTD: 1. Dyshpagia with a R 2 value of 0.33 (p value <0.001); 2. Raynaud's phenomenon with R 2 value of 0.28 (p<0.001). We did not find a significant association between any other demographic, clinical or serological variables and development of ILD in patients with MCTD. Conclusions: Dysphagia is one of the symptoms of esophageal involvement in patients with autoimmune connective tissue disorders. An association of dysphagia with the development of ILD in our study is in harmony with the existing literature, wherein esophageal dysmotility has been described in a cluster of patients with MCTD and ILD. Scant data, primarily case reports, suggest an association of Raynaud's phenomenon with development of ILD in patients with undifferentiated CTD. To our knowledge, this is the first study highlighting the association of Raynaud's phenomenon with development of ILD in a subset of patients with MCTD. This study is limited by its small size and retrospective nature. Additionally, the mechanistic aspects of this association between Raynaud's phenomenon and ILD remain unexplored. The association of easily elicited historical and clinical features of MCTD with subtle, but worrisome, pulmonary pathology carries the promise of sensitizing the unsuspecting clinician about the entity of ILD in MCTD. References: Colin G et al. Clinical study of interstitial lung disease in mixed connective tissue disease. Rev Mal Respir. 2010 Mar;27(3):238–46 Bodolay E et al. Evaluation of interstitial lung disease in mixed connective tissue disease (MCTD)Rheumatology 2005;44:656–61 Gunnarsson R et al. Prevalence and severity of interstitial lung disease in mixed connective tissue disease: a nationwide, cross-sectional study. Ann Rheum Dis 2012; 71:1966–72 Szodoray P et al. Distinct phenotypes in mixed connective tissue disease: subgroups and survival. Lupus (2012) 21, 1412–22 Sheehan NJ. Dysphagia and other manifestations of oesophageal involvement in the musculoskeletal diseases. Rheumatology (Oxford). 2008 Jun;47(6):746–52 Coates A et al. Dyspnea in a patient with Raynaud's phenomenon: the uncovering of interstitial lung disease. Pediatr Pulmonol. 2012 Sep;47(9):926–7 Disclosure of Interest: None declared